Artificial Psychosocial Framework for Affective Non-player Characters - Klinkert, Lawrence J.; Clark, Corey (Advances in Artificial Intelligence and Applied Cognitive Computing, 2021)
Video game designers express a need for a tool to create a human-like Non-Player Character (NPC) that makes contextually correct decisions against inputs performed at unforeseen times. This tool must be able to integrate with the designer’s current game engine, such as the Unreal Engine. To make an NPC more human-like, we use psychology theories, specifically, emotions in decision making, such as the ideas proposed by A. Damasio. This approach allows an NPC’s psychology to connect directly to the underlying intrinsic motivations that drive players. This paper presents the “Artificial Psychosocial Framework” (APF) and defines a new class of NPC known as an “Affective NPC” (ANPC). APF utilizes an ANPC’s personality, perceptions, and actions to generate emotions, which influences the social relationship they have with other ANPCs. Additionally, APF considers the generation of emotions as an ambivalent hierarchy and classifies the representation of a personality and social relation. APF can work in tandem with existing AI techniques, such as Fuzzy Logic, Behavior Trees, Utility Theory, and Goal-Oriented Action Planning, to provide an interface for developers to build emotion-centric gameplay. APF is a library for designers to use as a plug-in to a familiar game engine, such as the Unreal Engine. On the macro-level, APF uses the “Cognitive Appraisal Theory” (CAT) of emotions. On the micro-level, psychological models are chained together to determine the emotional state and social relation. The personality of an ANPC is represented by the Big Five: “Openness, Consciousness, Extroversion, Agreeableness, and Neuroticism,” also called the OCEAN model. The emotions of an ANPC are described by the “Ortony, Clore, and Collins” (OCC) model. The social relation between ANPCs uses the “Liking, Dominance, Solidarity, and Familiarity” (LDSF) model. This paper demonstrates APF by simulating a scenario from the “Dennis the Menace” setting, where each Dennis is an ANPC with a different personality mapped to a Myers-Briggs type indicator. The results demonstrate how a different personality profile will cause varying emotional states, responses, and actions for the two simulated ANPCs in the same simulated scenario.